Analyse procrustéenne généralisée de la forme du bec chez la poule locale et la pondeuse industrielle - BELMOKHTAR, Amani; REGUIEG, Basma (My University, 2021)
The Geometric morphometry MG is a powerful tool to identify and visualize changes in the conformations of the beak. In this work, the shape of the beak in industrial and local laying hens was analyzed by the use of modern morphometry techniques based essentially onthe configuration of landmarks via the Procruste overlay on digitized images of the slats on the upper side. The digitization of the images using the tpsDig software made it possible to retain 13 homologous landmarks on the upper mandible of each beak. The objective of the current studywas to study and quantify the variability of beak shapes in 64 laying hens (31 local hens and 33 commerciallaying hens).Principal Component Analysis (PCA) allowed us to extract 4 PC wichexplain 88.5% of the beak shape variability. On the other hand, the Factorial Discriminant (AFD) analysis,Hotteling test and the Mahalanobisd istance showed a significant difference (P 0.001) between the two genotypes for the beak shape. The results of this preliminary study are interesting since they make it possible to better visualize the conformation of the beak and exploit this variability in selection programs to obtain birds with beaks more adapted to some breeding conditions, and it could be a good alternative for beak trimming.
Keywords: Local chicken, laying hen, Beak shape, Morphometry-geometric